Climate fluctuations during the Ordovician-Silurian transition period in South China: Implications for paleoenvironmental evolution and organic matter enrichment - Chen, Weizhen; Tian, Jingchun; Lin, Xiaobing; Liang, Qingshao; Wang, Xing; Yi, Dingxin; Li, Yuanyuan (Palaeogeography, palaeoclimatology, palaeoecology, 2023)
The Ordovician-Silurian (OS) transition witnessed dramatic tectonic, climatic, marine, and biological coevolution, during which organic-rich black shale was widely deposited and is considered an important source rock. However, the potential links between the differential enrichment pattern of organic matter and climate fluctuations and paleoenvironmental evolution during this period are still unclear. In this paper, the Late Ordovician-early Silurian black shale in a JieLong (JL) section in South China was identified by graptolitic fossils, total organic carbon (TOC) content, X-ray diffraction (XRD), scanning electron microscopy (SEM) and geochemical analysis. The results show that the provenances of sedimentary rocks are all granodiorite-like. According to the variations in the TOC content and geochemical indicators, four layers are delineated. Under warm and humid climatic conditions, sea level rise and unstable seasonal upwelling led to Unit 1 organic matter enrichment controlled by high primary productivity, anoxic conditions and effective smectite production. Unit 2 organic matter burial was controlled by cold, arid and oxic environmental conditions, but primary productivity was still relatively high. After the end of the glacial period, warm and humid climatic conditions and rapid transgression were the main factors affecting the burial of organic matter in Unit 3. Under hot and humid climate conditions, higher terrigenous detrital inputs and unfavourable preservation environments, the dilution of organic matter in Unit 4 was accelerated. The corrected chemical index of alteration (CIAcorr) values show that the study area experienced a climate change of alternating cold and warm conditions in response to the climate fluctuation during the glacial-interglacial period. The CIAcorr value is negatively correlated with the TOC content, while the generation of available clay minerals (smectite) in warm and humid climates is usually consistent with the enhanced burial flux of organic matter, supporting the important role of climate fluctuations in the accumulation of organic matter. Finally, a comparison of the data from the present study with geochemical data from different profiles in South China reveals the role of climatic fluctuations during the OS transition in controlling paleoenvironmental evolution and organic matter enrichment, while such a heterogeneous factor is usually associated with global or regional geological events. Our study highlights this differential enrichment mechanism as a combined response of multiple factors and provides important implications for glacial-interglacial organic matter enrichment mechanisms. •Rapid changes of weathering indices imply climatic fluctuations during the Late Ordovician-Early Silurian.•Four different patterns were established for organic matter accumulation across the O/S.•Climate fluctuations and the heterogeneity nature of ocean systems explain the regional variations of OM accumulation.